On the issue of diagnosis and treatment of prosopalgia - Balkova, Неллі; Yanishevska, Лілія (Psychosomatic Medicine and General Practice, 2019)
This is a conference abstract from the ІІ Scientific-practical conference "Psychosomatic medicine: science and practice". It is dedicated to the issue of diagnosis and treatment of prosopalgia. 56 patients were consulted who consulted a neurologist with complaints of facial pain. In 26 of them, the pain was trigeminal, in 12 was due to arthrosis and arthritis of the temporomandibular joints (TMJ), chronic spasm of chewing muscles, and 18 patients showed signs of overloading of the TMJ and spastic response of chewing muscles to loading. All patients had anxiety-depressive disorders of varying degrees. Treatment of patients with dysfunction of the TMJ and masticatory muscles included the appointment of pregabalin, gabapentin or antidepressants, treatment with an orthodontist, performing exercises of articulatory gymnastics. The work performed showed the high diagnostic value of ultrasound of the TMJ and elastography of the chewing muscles in the initial diagnosis of prosopalgia.